Rationale for the use of protein-carbohydrate mix in the technology of disperse products - Slashcheva, Alina; Nykyforov, Radion; Popova, Svitlana; Korenets, Yurіi (Eastern-European Journal of Enterprise Technologies, 2016)
The possibility of using skim milk proteins and pectin of dogberries and sloes is considered. The high-quality whipped system was obtained based on the protein-carbohydrate clot and berry puree. This was possible due to the activation of the functional components of the berry puree in their joint whipping, due to the presence of the surface-active sodium caseinate and stabilizing properties of pectin. As a result of the controlled interaction of these substances, calcium pectate, and protein-carbohydrate complexes are formed, which ultimately improves the system viscosity. The content of essential ingredients in the mixes, including the protein-carbohydrate clot (PCC) with a concentration of 65...70 %; berry puree – 15...20 %, and sugar – 15 % was determined. Based on the experimental data, the production process parameters of the protein-carbohydrate mix (PCM), including preparation of raw materials; solubilization of protein-carbohydrate clot proteins; solubilization of berry puree pectin; mixing of the protein-carbohydrate clot and modified berry puree; cooling of the system to 4±2°C were determined. It was found that the protein-carbohydrate mix (PCM) can be used in technologies of frozen dessert products under certain process conditions (temperature, pH). The studies confirm the feasibility of the PCM use in technologies of frozen dessert products both in terms of effectiveness and nutritional value. The developed technology is low-waste, resource-saving and simple.